The Influence of Hedonic Shopping, Fashion Involvement, and Shopping Lifestyle on Impulse Buying - Oktavia, Intan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
In the growing trend of increasing shopping habits among the public, Uniqlo remains one of the well-known brands frequently sought after by consumers. This study aims to analyze the influence of Hedonic Shopping, Fashion Involvement, and Shopping Lifestyle on Impulse Buying among Uniqlo consumers at Lippo Plaza Mall Sidoarjo. The study employs a quantitative approach using a survey method via a questionnaire administered to 103 respondents selected through accidental sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software.The results of the study indicate that: (1) Hedonic Shopping does not significantly influence Impulse Buying (β = 0.138; p = 0.309); (2) Fashion Involvement has a significant positive effect on Impulse Buying (β = 0.350; p = 0.010); (3) Shopping Lifestyle does not have a significant effect on Impulse Buying (β = 0.175; p = 0.216). Simultaneously, the three independent variables significantly influence Impulse Buying with an R² value of 0.264, meaning that 26.4% of the variation in Impulse Buying is influenced by these three variables, while 73.6% is influenced by factors outside the model.Based on these findings, it is concluded that Fashion Involvement is the dominant factor influencing Impulse Buying behavior among Uniqlo consumers in Sidoarjo. The practical implication of this study is the need for marketing strategies focused on strengthening consumer involvement in fashion, such as through collaborations with influencers or the launch of limited-edition products, to increase impulsive purchases.